Effectiveness of rational emotive behavior therapy on the “Kancani” web application on stress levels of junior high school students - Maghfirani, Faradisa Laila; Mardhiyah, Zahrina (Jurnal Psikologi, 2024)
Background: Adolescents frequently experience substantial emotional changes, making them vulnerable to stress, particularly distress, which can lead to adverse effects such as fear, anxiety, and frustration due to incongruence between expectations and irrational beliefs. Consequently, addressing negative stress in adolescents requires the development of rational thinking and the ability to confront irrational beliefs effectively. Purpose: This study aims to assess the effectiveness of REBT interventions delivered through the "Kancani" web application in examining stress levels among junior high school students. Method: This study employed a quasi-experimental design with a one-group pretest-posttest approach, involving 22 participants.The purposive sampling technique was employed to select participants. An intervention consisting of 9 sub-modules was provided over a period of 2 weeks. The measuring instrument used was the DASS-42 scale, especially those measuring the stress scale consisting of 14 items (α = .881). Findings: The results obtained were a decrease in the average stress level of participants, t(21) = 2.141, p = .044, Cohen’s d = 0.456. Implication: Web Application “Kancani” is effective for decreasing stress levels of junior high-school. Prompting students to use kancani regularly and teacher evaluate it.